King Lear - Shakespeare, William, 1564-1616.; Foakes, R. A. (London : AS, 2004)
Presents the annotated text of Shakespeare's drama in which King Lear disinherits his favorite daughter when she speaks out against him and splits his kingdom between his other two daughters who are secretly plotting against him, and includes introductory notes, abbreviations and references, and an index.
Includes bibliographical references (p. 418-429) and index.
Adult.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Avarice -- Drama; Fathers and daughters -- Drama; Inheritance and succession -- Drama; Kings and rulers -- Drama; Lear, King (Legendary character) -- Drama; English drama; Father-daughter relationship -- Drama; Greed -- Drama; Inheritance and succession -- Drama; Kings and rulers -- Drama; Lear, King (Legendary character) -- Drama; Tragedies